2006
DOI: 10.1016/j.compscitech.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the glass fibre sizing composition and the surface quality of sheet moulding compounds (SMC) body panels

Abstract: The characteristics of thermosetting composite materials such as SMC are affected by the presence of reinforcements as a result of surface-matrix interactions. Surface treatments or sizings can significantly affect such interactions; hence the sizing selection may significantly affect SMC characteristics. The wetting properties of the unsaturated polyester matrix on glass fibres with different sizings have been studied by contact angle determination. In addition, the permeability of the glass fibres as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
13
0
3
Order By: Relevance
“…Interphases with gradual or monotonic change of mechanical properties and composition rather than homogeneous properties are highly expected, since in such case mechanical stresses can be efficiently transferred from matrix to reinforcement and the concentration of mechanical and thermomechanical stresses at this area can be greatly avoided [5]. Recent progresses in mechanical characterisation on interphases in combination with adhesion strength measurement and real composite mechanical tests indicated the presence of an interphase with mechanical property gradients leading to high mechanical properties [6][7][8][9][10][11]. As there is a steadily increasing interest in the use of thermoplastic composites in different fields, such as construction, automotive industries and aeronautic industries, in the field of GF reinforced thermoplastic composites various strategies have been developed in order to tailor the interphase characteristics, which mainly focused on the modification of GF surface or matrix, aiming at enhancing the GF-matrix adhesion strength, such as by enhancing GF-matrix compatibility, mechanical interlocking, and acid-base interaction [1][2][3][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interphases with gradual or monotonic change of mechanical properties and composition rather than homogeneous properties are highly expected, since in such case mechanical stresses can be efficiently transferred from matrix to reinforcement and the concentration of mechanical and thermomechanical stresses at this area can be greatly avoided [5]. Recent progresses in mechanical characterisation on interphases in combination with adhesion strength measurement and real composite mechanical tests indicated the presence of an interphase with mechanical property gradients leading to high mechanical properties [6][7][8][9][10][11]. As there is a steadily increasing interest in the use of thermoplastic composites in different fields, such as construction, automotive industries and aeronautic industries, in the field of GF reinforced thermoplastic composites various strategies have been developed in order to tailor the interphase characteristics, which mainly focused on the modification of GF surface or matrix, aiming at enhancing the GF-matrix adhesion strength, such as by enhancing GF-matrix compatibility, mechanical interlocking, and acid-base interaction [1][2][3][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For real reinforcements sized with the complete sizing formulation, it was proposed that silane coupling agent enriches on the sizing/GF interface, while the polymeric film former predominates on the sizing/ air interface, hence polymeric film former and polysiloxane network form an interpenetrating network (IPN) with gradual change of chemical composition from silane coupling agent dominated phase to polymeric film former enriched phase [29,35]. Literature addressing the formation of interphase dependence of sizing structure based on the complete sizing package is very limited [9][10][11]36]. In this study, silane coupling agent and polymeric film former were applied sequentially on as-spun GF at different stages, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, glass carry and fiber orientation are also discussed in many publications as major material flow issues. [6][7][8][9] As previously mentioned, the heavy truck industry, being an industry where weight savings is critical, offers the largest potential for SMC growth. The trucking industry requires parts with high strength and stiffness, yet surface quality is important.…”
Section: Research Background and Objectivesmentioning
confidence: 99%
“…In order to use engineering design guidelines, it has been shown that standard failure criteria in combination with adapted degradation models can be used to cover the non-linear material behaviour [26]. Other research groups have combined local endless fibre reinforcements with short fibres or long fibres [31][32][33][34] in order to increase both fibre volume content and mechanical properties instead of using grids.…”
Section: Introductionmentioning
confidence: 99%